Case Report: Deep sternal wound infection caused by Mycoplasma hominis after cardiac surgery - Wang, Zhaohui; Shi, Yong; Chen, Yu; Chen, Lijun (Frontiers in Cardiovascular Medicine, 2025)
Deep sternal wound infection (DSWI) caused by Mycoplasma hominis after cardiac surgery is very rare and easily overlooked. This paper reports the case of a patient with DSWI after cardiac surgery. The patient had an unexplained fever postoperatively. On the seventh day after surgery, the incision opened, and there was pus leakage. On the 11th day after surgery, the pus culture indicated Mycoplasma hominis infection. The patient was cured after treatment with omadacycline and secondary surgery.